Influence of solar activity on water clusters. Annual variations 2015—2019 - Shevchenko, I.V. (Reports of the National Academy of Sciences of Ukraine, 2022)
The variations of solar activity and distribution of solar energy due to the rotation of the Earth around its axis and around the Sun exert a strong influence on water clusters, as a result of which their chemical reactivity in hydrolytic processes can vary in a very wide range. This phenomenon is well manifested in the hydrolysis of the phosphoric acid esters. The 5-year regular investigations (2015—2019) of the hydrolysis of triethylphosphite in acetonitrile show that the rate of this reaction with all other conditions being equal displays diurnal, very large annual variations, and is also modulated by the 11-year cycles of solar activity. Since water is a necessary constituent in all forms of life, the discovered diurnal and annual variations of water clusters’ reactivity may underlie the biological circadian and circannual rhythms. The results obtained also point to the fact that the chemical reactivity of water clusters depends on the geographic latitude, and, in summer and winter, it can be significantly different at the same time in the Northern and Southern hemispheres. At the equator, where there should be no seasonal differences, measurements of the rate of triethylphosphite hydrolysis may become an independent method for assessing the solar activity.